2021
DOI: 10.4103/injms.injms_107_20
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Serum Vitamin D Levels and Assessing its Influencing Factors among Antenatal Women in a South Indian Town-Kumbakonam Urban Rural Epidemiological Study

Abstract: Background: Adequate antenatal Vitamin D intake is essential for maternal and fetal health during pregnancy and avoidance of adverse outcomes. The normal and abnormal concentrations are not well established in the different parts of the world with varying customs in life. We intended to estimate the normal random serum Vitamin D levels among antenatal mothers in the first trimester and whether factors such as age, weight, and religion have any influence on the same. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Multiparity was associated with decreased Vitamin D levels ( 23 ). Religious factors like staying indoors and restrictive clothing too play an important factor in Vitamin D deficiency ( 24 , 25 ), and studies have shown that socioeconomic status has a considerable impact on Vitamin D levels ( 26 ). Obesity is also proven to be a risk factor for Vitamin D deficiency ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multiparity was associated with decreased Vitamin D levels ( 23 ). Religious factors like staying indoors and restrictive clothing too play an important factor in Vitamin D deficiency ( 24 , 25 ), and studies have shown that socioeconomic status has a considerable impact on Vitamin D levels ( 26 ). Obesity is also proven to be a risk factor for Vitamin D deficiency ( 27 ).…”
Section: Methodsmentioning
confidence: 99%